Decoding Currency Fluctuations: Exploring Exchange Rate Dynamics Through Generalized Sup ADF Tests In Emerging Markets - Rafiq Ahmed , Aftab Hussain Tabasam (correspondence Author) , Shahid Mahmood , Nowsherwan Sarwar , Lubna Zafar , Syed Tehseen Jawaid (Migration Letters, 2024)
The present empirical research is a pioneering study to identify the multiple episodes of bubbles in Pakistan’s economy’s nominal rupee-dollar exchange rate for three data sets: annual, quarterly, and monthly. The high-frequency data sets benefit from the close analysis of the dilemma. The famous Generalized Supremum Augmented Dickey-Fuller GSADF test determines the explosive multiple bubbles in Pakistan’s exchange rate. Annual data r[1]evealed that the two episodes of bubbles were first from 1988 to 2003 and second from 2018 to 2019. The quarterly data set reported that there are three episodes of the bubble: the first starts from the 1st quarter of 2009 to the 2nd quarter of 2015, the second from the 3rd quarter of 2015 to the 3rd quarter of 2017, the third starts from the 4th quarter of 2017 to 2nd quarter of 2021. Finally, the monthly data set reports a single bubble episode from 2009M03 to 2021M06—such bubbles in the exchange rate call for instability in forthcoming trade contracts. Pakistan’s government should adopt tight monetary and fiscal policies to avoid exchange rate bubbles in the future.